2020
DOI: 10.18502/ijm.v12i5.4607
|View full text |Cite
|
Sign up to set email alerts
|

Quorum sensing-regulated functions of Serratia marcescens are reduced by eugenol

Abstract: Background and Objectives: Serratia marcescens has emerged as a nosocomial pathogen responsible for human infections, where antibiotic resistance further complicates the treatments. In S. marcescens, biofilm formation and virulence factor production are controlled via quorum sensing (QS) system. QS is a signaling system that enables gene regulation to control diverse physiological functions in bacteria. Essential oils have shown to be potential in diminishing the pathogenicity and virulence of drug-resistant b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…[20][21][22][23][24] Numerous studies have shown that ATCC 9027, ATCC 6538 and ATCC 13880 are similarly susceptible to antibacterial activity as other strains and species, 22 25-32 and that these strains have similar virulence or virulence factors when used in other species or with human cells. [33][34][35][36][37][38][39] As we expected, and similar to results we have reported previously for products on the American market, 9 most CLCs meet or exceed the primary criteria set forth by the ISO standard. The only exception found in this study was when renu Multiplus, All Clean Soft, and Kombilösung Super were challenged with Serratia marcescens.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[20][21][22][23][24] Numerous studies have shown that ATCC 9027, ATCC 6538 and ATCC 13880 are similarly susceptible to antibacterial activity as other strains and species, 22 25-32 and that these strains have similar virulence or virulence factors when used in other species or with human cells. [33][34][35][36][37][38][39] As we expected, and similar to results we have reported previously for products on the American market, 9 most CLCs meet or exceed the primary criteria set forth by the ISO standard. The only exception found in this study was when renu Multiplus, All Clean Soft, and Kombilösung Super were challenged with Serratia marcescens.…”
Section: Discussionsupporting
confidence: 89%
“…However, these strains are a critical and commonly used piece of evidence when testing for sterility and microbial contamination, as well as biofilms 20–24. Numerous studies have shown that ATCC 9027, ATCC 6538 and ATCC 13880 are similarly susceptible to antibacterial activity as other strains and species,22 25–32 and that these strains have similar virulence or virulence factors when used in other species or with human cells 33–39. As we expected, and similar to results we have reported previously for products on the American market,9 most CLCs meet or exceed the primary criteria set forth by the ISO standard.…”
Section: Discussionsupporting
confidence: 86%
“…QS signal molecules N-acylhomoserinelactones( AHL ,C4 and C6) regulate different genes responsible for production of various virulence factors, secondary metabolite, prodiogosin and biofilm formation in Serratia [33][34][35] . Eugenol, a plant metabolite could prevent the production of QS-controlled virulence factors like pigment prodigiosin, protease and hemolysin.The QSmediated biofilm formation stages such as swarming motility, formation of microcolony and extracellular polysaccharide production were inhibited and expression of genes responsible for QS system, adhesion, motility, and biofilm formation were down-regulated 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Another plant metabolite able to prevent the production of QS-controlled virulence factors and related to BF formation is eugenol [141]. Fekrirad et al indicated that this catechol was able to prevent the production of QS-controlled virulence factors, such as pigment prodigiosin, protease, and hemolysin in Serratia marcescens [142]. Specifically, they found that eugenol affected swarming motility, the formation of the microcolony, and extracellular polysaccharide via the downregulation of correlated genes.…”
Section: Quorum Sensing Inhibitorsmentioning
confidence: 99%